SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KARYAWAN TELADAN DI UNIVERSITAS BANTEN JAYA MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Raden Kania; Rustam Effendi; Anggun Risdiansyah (Program Studi Sistem Informasi, Universitas Banten Jaya, 2021)
Banten Jaya University (UNBAJA) is one of the educational institutions engaged in technology and information, which part of the system has been computerized. But in development there is still a work system that is done manually. Data processing from information that is done manually can be said to be far from the goal, given the importance of effectiveness and efficiency of employee performance. Therefore, Banten Jaya University must be able to improve the quality and quality of employee performance by holding a Decision Support System using the simple addinue weight (SAW) method, which is a computer-based information system and also includes a system with a knowledge management basis, used to support decision making in an organization or company. The decision support system for selecting exemplary employees at the University of Banten Jaya (UNBAJA) can be run well. The development model used is Waterfall. The stage of the process of making a decision support system for selecting exemplary employees at the University of Banten Jaya (UNBAJA) begins with making a design, determining the flow of the work system, making a coding program, making a design view. The decision support system for selecting exemplary employees at the University of Banten Jaya (UNBAJA) uses a PHP MySQL database server. From the test results using the Black Box, the results show that the system testing decision support system for selecting exemplary employees at the University of Banten Jaya (UNBAJA) is successful and can be used and operated well.